The Validity of the Geometry of the Hilal Position in the Hilal Observation Report at the International Astronomical Center (IAC) in 1436–1446 H - George As'ad Haibatullah El Masnany; Elly Uzlifatul Jannah; Novi Sopwan (University of Muhammadiyah Sumatera Utara, 2026)
This study examines the validity of 641 crescent moon sighting reports published by the International Astronomical Center (IAC) during the period 1436–1446 H using geometric parameters and the visibility thresholds of the Odeh (2004) model. The reports consist of 231 naked-eye observations, 57 binocular observations, 27 telescopic observations, 60 CCD (Charge-Coupled Device) observations, as well as several combinations of methods. This research employs a descriptive-analytical approach with computational astronomical methods. The IAC reports were collected through documentation techniques and subsequently processed by recalculating the positions of the Moon and the Sun using the VSOP2000 and ELP2000 ephemerides in a topocentric framework at sunset and best time. The results show that naked-eye observations with ArcV 7.4989°, ArcL 9.228°, W 0.2011′, DAz 0.8029°, and lag −31.0593 minutes fall within Zones A–B; binocular observations with ArcV 3.9893°, ArcL 9.4993°, W 0.1967′, DAz 0.3329°, and lag 17.9419 minutes fall within Zones C–B; telescopic observations with ArcV 2.6134°, ArcL 6.9358°, W 0.1162′, DAz 0.1195°, and lag 15.0096 minutes fall within Zones D–C; and CCD observations with ArcV 3.4399°, ArcL 6.7413°, W 0.1033′, DAz 0.2769°, and lag 17.6455 minutes fall within Zone D. These findings indicate the necessity of automatically integrating geometric parameters to enhance the accuracy and accountability of crescent moon reporting at the IAC.